Instructional Behavior of Teachers of Physical Education and Sports for the Intermediate and Secondary Schools by Hamdan Tool to Observe and Analyze the Overall Class Interaction. - Abdelhafid Kadri (sports creativity, 2025)
With the development of curricula, strategies, methods and methods of education, the role of the professor has also developed and is no longer a mere conveyor of knowledge, but has become a guide, critique and guide for the learner in how to acquire self-knowledge. Physical education and sports as a teaching material do not deviate from this conceptual framework in order to reach the level of mastery, which requires an objective measurement of this behavior during the course of the lesson, in which the teacher and learner interact. This measurement allows us to evaluate this behavior so that it can be strengthened, We can evaluate and then conduct the behaviors of both the teacher and the learner, and in this regard, many tools emerged especially in the Arab environment, where Muhammad Ziad Hamdan designed his instruments to observe the overall classroom interaction, and through the results of many studies the lack of interest of some professors of physical education and sports Interaction with the learner, and also traditional in the assessment and evaluation professor by education inspectors lacked ways to reduce the objectivity and the preparation and composition professor programs Able to interact effectively. In order to achieve the objectives of the research, an exploratory study was conducted in the presence of some physical education and sports classes for the two classes in the Barika class during the 2017-2018 academic year. The aim was to know the field of the pedagogic behavior in the physical and sports education classes for the intermediate and secondary schools. The descriptive approach was used by regular observation of teaching behavior between teacher and students.